Construction of hierarchical Co–Fe oxyphosphide microtubes for electrocatalytic overall water splitting - Zhang, Peng (2019)
Development of efficient electrocatalysts is a crucial requirement to build water splitting systems for the production of clean and sustainable fuels. This goal could be achieved by fine‐tuning the composition and structure of the electrocatalytic materials. Here, a facile self‐templated synthetic strategy is developed for the fabrication of hierarchical Co–Fe oxyphosphide microtubes (MTs). Fe‐based metal–organic compound microrods are first synthesized as the self‐sacrificing template. Afterward, the Fe‐based precursors are converted into hierarchical Co–Fe layered double hydroxide MTs through a hydrothermal approach, which are then transformed into the hierarchical Co–Fe oxyphosphide MTs by a phosphidation treatment. Benefiting from the synergistic effect of the compositions and the advantages of the hierarchical hollow structure, the obtained electrocatalyst exhibits enhanced performance for overall water splitting.